Metabolic syndrome severity score and the progression of CKD. (13th July 2021) - Wu, Mingyang; Shu, Yanling; Wang, Lulin; Song, Lulu; Chen, Shuohua; Liu, Yunyun; Bi, Jianing; Li, Dankang; Yang, Yingping; Hu, Yonghua; Wang, Youjie; Wu, Shouling; et al.
Abstract: Background: Metabolic syndrome severity, expressed by the continuous metabolic syndrome risk score (MetS score), has been demonstrated to be able to predict future health conditions. However, little is known about the association between MetS score and renal function. Methods: A total of 22, 719 participants with normal renal function abstracted from the Kailuan Study were followed from 2006 to 2016. The new onset of chronic kidney disease (CKD) was defined as eGFR <60 ml/min per 1.73 m 2 and/or proteinuria >300 mg/dl. Progressive decline in renal function was defined as an annual change rate of eGFR below the 10th percentile of the whole population. Results: In the multivariate‐adjusted model, we found that the risk of progressive decline in renal function increased consistently with the MetS score, with an odds ratio of 1.49 (95% CI, 1.28, 1.73) for those subjects>75th percentile compared with those <25th percentile. Additionally, a high MetS score was found to be associated with an increased risk of CKD, with a hazard ratio of 1.53 (95% CI, 1.33, 1.78) for subjects >75th percentile compared with those <25th percentile. Conclusions: Our findings suggested that the MetS score was associated with an increased risk of a progressive decline in renal function and was also a strong and independent risk factor for the development of CKD. These findings provide evidence of the potential clinical utility of the MetS score for assessing metabolic syndrome severity to detect the risk of decreased renal function and CKD.